Efektivitas model pembelajaran CORE terhadap hasil belajar PAI dan budi pekerti - Alfiani, Defi; Pahrudin, Agus; Kuswanto, Riyan Terna (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
Islamic Religious Education (PAI) learning at the junior high school level should not merely focus on one-way content delivery but should also promote students’ conceptual understanding at the C2 cognitive level (understanding) as a foundation for higher-order thinking. However, learning outcomes remain low, as students have not been able to optimally internalize the material due to conventional & less interactive instructional practices. This study aims to analyze the effectiveness of the CORE (Connecting, Organizing, Reflecting, Extending) learning model in improving students’ learning outcomes in PAI. This study employed a quantitative approach using a quasi-experimental method with a post-test only control group design involving 60 students as research participants. Data were collected through a multiple-choice learning achievement test. The normality test results showed significance values of 0.081 & 0.158 (p > 0.05), while the homogeneity test yielded a significance value of 0.763 (p > 0.05), indicating that the data were normally distributed & homogeneous. The independent sample t-test revealed a significance value of 0.001 < 0.05 with t = 3.599, indicating a significant difference between the experimental & control groups, with higher learning outcomes observed in the experimental group. These findings imply that the CORE model is effective as a student-centered learning strategy that promotes active engagement, strengthens reflective processes, & assists students in constructing & reinforcing meaningful conceptual understanding. Abstrak Pembelajaran Pendidikan Agama Islam (PAI) di SMP idealnya tidak hanya berorientasi pada penyampaian materi satu arah, tetapi juga mendorong pemahaman konsep pada ranah kognitif C2 sebagai dasar berpikir tingkat tinggi, namun hasil belajar masih rendah karena peserta didik belum mampu menginternalisasi materi secara optimal akibat pembelajaran yang masih konvensional dan kurang interaktif. Penelitian ini bertujuan untuk menganalisis efektivitas model pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) terhadap hasil belajar peserta didik pada mata pelajaran PAI. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi-experimental melalui desain post-test only control group yang melibatkan 60 peserta didik sebagai sampel penelitian. Teknik pengumpulan data dilakukan melalui tes hasil belajar berbentuk pilihan g&a. Hasil uji normalitas menunjukkan nilai signifikansi 0,081 dan 0,158 (p>0,05), serta uji homogenitas sebesar 0,763 (p>0,05), sehingga data dinyatakan berdistribusi normal dan homogen. Hasil uji t menunjukkan nilai signifikansi 0,001 < 0,05 dengan t = 3,599, yang menunjukkan adanya perbedaan signifikan antara kelas eksperimen dan kelas kontrol, di mana hasil belajar peserta didik pada kelas eksperimen lebih tinggi. Temuan ini mengimplikasikan bahwa model CORE efektif digunakan sebagai strategi pembelajaran yang berpusat pada peserta didik yang mampu mendorong keterlibatan aktif, memperkuat proses refleksi, serta membantu peserta didik dalam mengonstruksi dan memperkuat pemahaman konsep secara bermakna.